The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1182/asheducation-2015.1.420
|View full text |Cite
|
Sign up to set email alerts
|

The five key things you need to know to manage adult patients with sickle cell disease

Abstract: The lack of a strong evidence base to guide the management of adults with sickle cell disease (SCD) makes it difficult for patients to receive high quality care outside of specialty centers. As there is a dearth of providers with sickle cell expertise, the purpose of this article is to identify some of the key things every provider who manages the care of adults with SCD should know. Managing adults with SCD requires excellent clinical skills, as it can affect every organ and cause life-threatening complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…The program directors' survey found that ,6% of graduates of adult training programs pursued careers in nonmalignant hematology, but there was little discussion of factors involved in this career choice. 5 Others have noted a decline in the number of physicians specializing in nonmalignant hematology careers such as care of patients with hemophilia and sickle cell disease, 7,8 and more recently, a group of hematologists published an overview calling for the need to expand the nonmalignant hematology workforce. 9 In this project, we surveyed recent graduates of a large academic hematology-oncology fellowship training program to determine postfellowship career pathways, determinants of those choices, and to specifically identify factors that may have influenced fellows' choices to pursue (or not to pursue) careers in nonmalignant hematology.…”
Section: Introductionmentioning
confidence: 99%
“…The program directors' survey found that ,6% of graduates of adult training programs pursued careers in nonmalignant hematology, but there was little discussion of factors involved in this career choice. 5 Others have noted a decline in the number of physicians specializing in nonmalignant hematology careers such as care of patients with hemophilia and sickle cell disease, 7,8 and more recently, a group of hematologists published an overview calling for the need to expand the nonmalignant hematology workforce. 9 In this project, we surveyed recent graduates of a large academic hematology-oncology fellowship training program to determine postfellowship career pathways, determinants of those choices, and to specifically identify factors that may have influenced fellows' choices to pursue (or not to pursue) careers in nonmalignant hematology.…”
Section: Introductionmentioning
confidence: 99%
“…As manifestações são diversas e podem acometer diferentes sistemas. No gastrointestinal e abdominal pode haver crises de dor, cálculos biliares, icterícia obstrutiva, hepatopatia; no sistema nervoso central, acidente isquêmico transitório, infarto, hemorragia cerebral; no cardiopulmonar, cardiomegalia, insuficiência cardíaca, infarto pulmonar, pneumonia; no urogenital, priapismo, hipostenúria, insuficiência renal crônica; na superfície cutânea-mucosa, pode apresentar palidez, icterícia e úlceras; no osteoarticular, dores, necrose asséptica da cabeça do fêmur, gnatopatia; nos olhos, retinopatia proliferativa, glaucoma; sistema hematopoiético, temos anemia, asplenia, esplenomegalia crônica e nas manifestações gerais, retardo da maturação sexual e maior suscetibilidade a infecções 2,3,4,10 . A síndrome torácica aguda é um tipo particularmente perigoso de crise vaso-oclusiva envolvendo os pulmões, que tipicamente se apresenta com febre, tosse, dor torácica e infiltrados pulmonares.…”
Section: Discussionunclassified
“…Accurate recording of previously prescribed doses of these analgesics could assist in informing subsequent hospital admissions, provide continuity of care and ensure that pain relief is individualised and appropriate. However, it remains necessary to monitor patients for opioid misuse or addiction (Lanzkron and Haywood 2015), and to review the effectiveness of any pain relief interventions used (Kotila et al 2015).…”
Section: Acute Vaso-occlusive Pain Assessment and Managementmentioning
confidence: 99%